Historically Grounded Symbolism and the Thematic Lacuna in Translation: The Translation of 'Treasure Island' into Kiswahili as 'Kisiwa Chenye Hazina' (Mwanga wa Lugha, 2019)
This paper avers that the available translations of Treasure Island in Kiswahili literature under the title Kisiwa Chenye Hazina are testimony to translation strategies producing unintended consequences in the target literature. The 1928 translation of Treasure Island by J. Johnson with revisions by M. Saidi in 1981 and the 1956 translation with revisions by Peter Kisia (1993) into Kiswahili as Kisiwa Chenye Hazina are illustrative of translations abounding with paucity of source text details, glossing over the meticulous descriptive details of the source text, blotching the richness of the figurative language in the source text; neutering the source text’s symbolism marked by its figurative language, characterization formats, scenery descriptions as well as names referring to people, places and things. The blotching of these foundational aspects of source text unconsciously generates partial thematic realizations in the target text. Whereas the source text intricately advances a rich medley of subtle subtext(s) suggestive of among other issues colonialism in varied facets, social class hierarchies, interaction between “respectable” society and the posterior sub-culture of piracy. A critical thematic analysis of the Kiswahili translations does not come across this subtext(s) of Treasure Island in Kisiwa Chenye Hazina. Instead, the translations reveal a pseudo-translation and fractional renditions—to use Toury’s (1984) terminology, they also exhibit myriad instances of trite paraphrases, translational shifts of source text descriptions, sceneries and characters, indistinct dialogues, unjustified additions and skewed renditions.